The Feeding Habits of Mesosauridae - Silva, Rivaldo R.; Ferigolo, Jorge; Bajdek, Piotr; Piñeiro, Graciela (Frontiers in Earth Science, 2017)
Mesosauridae comprises the oldest known aquatic amniotes which lived in Gondwana during the Early Permian. Previous work in the Uruguayan mesosaur-bearing Mangrullo Formation suggested that mesosaurids lived in an inland water body, inferred as moderately hypersaline, with exceptional preservational conditions that justified describing these strata as a Fossil-Lagerstätte. Exquisitely preserved articulated mesosaur skeletons, including gastric content and associated coprolites, from the Brazilian Iratí Formation in the State of Goiás (central-western Brazil) indicate excellent conditions of preservation, extending the Konservat-Lagerstätte designation to both units in the Paraná Basin. The near-absence of more resistant fossil remains, like actinopterygian and temnospondyl bones, demonstrates the faunistic poverty of the mesosaur-bearing “salty sea”. Our studies of the alimentary habits of mesosaurids through the use of stereoscopic microscopy, light and electronic microscopy, and X-ray diffractometry suggest that the diet of mesosaurids was predominantly composed of pygocephalomorph crustaceans (possibly not exceeding 20 mm in length). However, the presence of bones and bone fragments of small mesosaurs in the gastric content, cololites, coprolites, and possible regurgitalites may also indicate cannibalistic and/or scavenging habits. Cannibalism is relatively common among vertebrates, particularly during conditions of environmental stress, like food shortage. Likewise, the apparent abundance of pygocephalomorph crustacean fossils in the Iratí and Mangrullo Formations, outside and within the studied gastric, cololite, and coprolite contents, might have to do with environmental stress possibly caused by volcanic activity, in particular ash spread into the basin during the Early Permian. In this context, casual necrophagy on the dead bodies of small mesosaurs and large pygocephalomorphs might have been an alternative alimentary behavior adopted for survival in mesosaurs.